2002
DOI: 10.1021/tx025581f
|View full text |Cite
|
Sign up to set email alerts
|

A Planar Catechin Analogue as a Promising Antioxidant with Reduced Prooxidant Activity

Abstract: A planar catechin analogue (1H2), in which catechol and chroman moieties in (+)-catechin are constrained to be coplanar, is an efficient radical scavenger compared to the native catechin, and are nearly as effective as quercetin, a strong radical scavenger. The dianion (1(2-)) of 1H2 produced by the reaction of 1H2 with 2 equiv of tetramethylammonium methoxide reduced molecular oxygen (O2) to generate superoxide anion (O2*-). The resulting radical anion (1*-) from 1H2 underwent intramolecular proton transfer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 39 publications
1
13
0
1
Order By: Relevance
“…The one electron-transfer reaction from dianion to molecular oxygen proceeds to form O2 -. The same reaction is also shown by the dianion (PCA 2-) of PCA, forming O 2 -by electron-transfer oxidation from PCA 2-to O2 as conˆrmed by a low-temperature ESR (23). A characteristic ESR g// value of 2.070 due to O2 -, together with an ESR g// value of 2.050 for protonated O2 -(HO2  ) was observed for an O2-saturated MeCN solution of PCA and 2 equiv of MeO -at 77 K, as shown in Fig.…”
Section: Reduced Antioxidant Activitysupporting
confidence: 53%
“…The one electron-transfer reaction from dianion to molecular oxygen proceeds to form O2 -. The same reaction is also shown by the dianion (PCA 2-) of PCA, forming O 2 -by electron-transfer oxidation from PCA 2-to O2 as conˆrmed by a low-temperature ESR (23). A characteristic ESR g// value of 2.070 due to O2 -, together with an ESR g// value of 2.050 for protonated O2 -(HO2  ) was observed for an O2-saturated MeCN solution of PCA and 2 equiv of MeO -at 77 K, as shown in Fig.…”
Section: Reduced Antioxidant Activitysupporting
confidence: 53%
“…It is also accepted that oxidation of Cat 2− to produce Cat a ·− is are generated via an electron transfer oxidation of Cat 2− by molecular oxygen. 44,45) Therefore, the proton and electron are transferred in one kinetic step corresponding to following the diagonal of the rectangle in Fig. 4a, labeled concerted PCET, avoiding generation of the high-energy intermediates.…”
Section: Cyclic Voltammetry Of O 2 In the Presence Of Flavonoidsmentioning
confidence: 99%
“…Electron spin resonance (ESR) spectroscopy can provide direct evidence of the formation of free radicals in chemical and biological reactions. Because ESR generates signals only in molecules with unpaired electrons, it is very selective and can be used even in situations where thousands of other compounds are present (Fukuhara et al, 2003). Some authors demonstrated such results of free radical scavenging activities of propolis and some plants were examined using ESR spectroscopy (Scheller et al, 1990;Rapta et al, 1995;Cal- Scheller et al (1990) stated that the DPPH signal intensity was inversely related to the concentration of the ethanolic extract of propolis (EEP) and due to the reaction time.…”
Section: Estimation Of Antioxidant Activity By Esr Measurementsmentioning
confidence: 99%